RETRACTED: SiC ultra -thin films for high-performance quantum spacecraft applications fabricated via nanosecond pulsed laser deposition and doping - Praveen Kumar Kanti; Prashantha Kumar H.G.; V. Vicki Wanatasanappan; Abhinav Kumar; Dhouha Choukaier; Subbulakshmi Ganesan; Tekalign Negash Kebede (PLoS ONE, 2025)
This research investigates the deposition, characterization of SiC ultra-thin films deposited by nanosecond pulsed Nd 3 ⁺ laser deposition technique and laser assisted doping. These SiC films possess better qualities in terms of surface roughness varying from 2–5 nm. Using an atom probe tomography (APT) and a transmission electron microscope (TEM), key elemental maps showed desirable concentrations of Si of ~50 at.% and C of ~48 at.% with minor elemental contents including O, Al, N, and B. These distributions indicate the material’s structural and chemical performance under laser assisted doping. I-V measurements reveal better electronic response, including low turn-on voltage, and high carrier mobility that makes these films suitable for quantum spacecrafts. This research stresses the review of laser fluence and doping as important parameters for modifying SiC thin films for future electronics and space applications.